Analisis Strategi Pemasaran Kopi Lokal di Pasar Global: Studi Kasus pada Kopi Kenangan - Daffa Reza Fahlevi; Rosi Rahmawati; Nadia Jasmine (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the marketing strategy of Kopi Kenangan, an Indonesian local coffee brand, in the context of the global market. The coffee industry is one of the fastest-growing sectors worldwide, supported by increasing consumption and lifestyle changes. Kopi Kenangan has emerged as one of the most successful local brands in Southeast Asia by implementing strategies that combine affordability, local cultural identity, product innovation, and digital transformation. Using a qualitative descriptive method with a literature study and case study analysis, this research identifies several key aspects of Kopi Kenangan’s marketing strategy, namely affordable pricing, innovative product development, rapid outlet expansion, digital marketing integration, and international expansion. The findings indicate that Kopi Kenangan’s strategy reflects a combination of global business practices and local cultural adaptation, which enables it to compete with established international brands such as Starbucks.